The DNAJA2 Substrate Release Mechanism Is Essential for Chaperone-mediated Folding - Baaklini, Imad (American Society for Biochemistry and Molecular Biology, 2012)
DNAJA1 (DJA1/Hdj2) and DNAJA2 (DJA2) are the major J domain partners of human Hsp70/Hsc70 chaperones. Although they have overall similarity with the well characterized type I co-chaperones from yeast and bacteria, they are biologically distinct, and their functional mechanisms are poorly characterized. We identified DJA2-specific activities in luciferase folding and repression of human ether-a-go-go-related gene (HERG) trafficking that depended on its expression levels in cells. Mutations in different internal domains of DJA2 abolished these effects. Using purified proteins, we addressed the mechanistic defects. A mutant lacking the region between the zinc finger motifs (DJA2-Δm2) was able to bind substrate similar to wild type but was incapable of releasing substrate during its transfer to Hsc70. The equivalent mutation in DJA1 also abolished its substrate release. A DJA2 mutant (DJA-221), which had its C-terminal dimerization region replaced by that of DJA1, was inactive but retained its ability to release substrate. The release mechanism required the J domain and ATP hydrolysis by Hsc70, although the nucleotide dependence diverged between DJA2 and DJA1. Limited proteolysis suggested further conformational differences between the two wild-type co-chaperones and the mutants. Our results demonstrate an essential role of specific DJA domains in the folding mechanism of Hsc70.